Perioperative Glucagon-Like Peptide-1 Receptor Agonists (GLP-1RA) and Gastric Point Of Care Ultrasound (POCUS) - Sivasenthil Arumugam; Hari Kalagara (CINQUILL Medical Publishers Inc., 2024)
Glucagon-like peptide-1 receptor agonists (GLP-1 RA) are frequently used for diabetes and weight loss management. The GLP-1 RA   drugs delay gastric emptying and are a concern for increased risk of aspiration in the perioperative period. Current recommendations to hold these medications before surgery are consensus based. Gastric point of care ultrasound (POCUS)   can provide information regarding nature and volume of gastric contents in these patients during the perioperative period. In this case series, we present three patients where gastric POCUS helped formulate a safer, alternative anesthetic plan. Anesthetic management varied depending on the situation, urgency and needs of the procedure. We recommend gastric POCUS in this group of patients to provide objective assessment of gastric contents.